Development of Pop-Up Book Media Social Aspects in Developing Early Children's Cooperation Capability - Konstantinus Dua Dhiu; Veronika Owa Mere (Universitas Negeri Semarang, 2025)
This research aims to: (1) produce media in the form of pop-up books to develop social skills in children aged 5-6 years, (2) to determine the level of suitability of pop-up book media for social aspects for children aged 5-6 years. The subjects in this research were children aged 5-6 years at SDK Olabolo One Roof Kindergarten, either in groups or individually. The stages used in this research include Analysis, Design, Development, Implementation and Evaluation. The data collection techniques applied consisted of documentation and distributing questionnaires. The media validation process is carried out through assessments by material experts, learning design experts and learning media experts. The data obtained was analyzed using qualitative and quantitative descriptive approaches. The results of research into the development of pop-up book media are as follows. 1) media expert trials are in the